Need for Thorough Standardization of CO2 Laser Evoked Potential Procedure. Issue 6 (November 2018) - Tudor, Katarina I.; Petravić, Damir; Krbot Skorić, Magdalena; Išgum, Velimir
Abstract : Purpose: The objective of this study was to determine normative values of laser evoked potentials and anthropometric correlations in a healthy middle-aged working population. Methods: In 51 subjects, CO2 laser stimulation was applied bilaterally onto dorsal surface of the feet, hands, and neck using constant duration of stimulus and beam diameter, changing just the intensity of stimulation. Amplitudes and latencies of the laser evoked potential negative–positive complex were recorded, and relationship with height, age and gender was statistically analyzed. Results: There was a significant correlation between the latencies obtained for feet, hands, and height. P2 amplitudes for feet, hands, and neck, and negative–positive pk-pk amplitudes for hands and neck correlated negatively with age. The values obtained did not differ significantly between male and female gender, except for N2 latencies for hands. Conclusions: Clinically useful reference values for laser evoked potentials in a healthy middle-aged population were provided, which are interesting from the physiological point of view.